2003
DOI: 10.1002/adfm.200304373
|View full text |Cite
|
Sign up to set email alerts
|

General Synthesis of Single‐Crystal Tungstate Nanorods/Nanowires: A Facile, LowTemperature Solution Approach

Abstract: The general large‐scale synthesis of a family of single‐crystalline transition metal tungstate nanorods/nanowires is easily realized by a hydrothermal crystallization technique under mild conditions using cheap and simple inorganic salts as precursors. Uniform tungstate nanorods/nanowires such as MWO4 (M = Zn, Mn, Fe), Bi2WO6, Ag2WO4, and Ag2W2O7 with diameters of 20–40 nm, lengths of up to micrometers, and controlled aspect ratios can be readily obtained by hydrothermal transformation and recrystallization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
296
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 449 publications
(313 citation statements)
references
References 82 publications
14
296
1
2
Order By: Relevance
“…Transition metal tungstates are important inorganic materials that are studied and applied widely in many fields [133]. Among these, Ag 2 WO 4 has attracted considerable attention because of their potential applications in fields as ionic conductivity [134], photocatalysis [135], sensors [136], microbial agents [137], photoluminescence properties [137,138].…”
Section: α-Ag 2 Womentioning
confidence: 99%
“…Transition metal tungstates are important inorganic materials that are studied and applied widely in many fields [133]. Among these, Ag 2 WO 4 has attracted considerable attention because of their potential applications in fields as ionic conductivity [134], photocatalysis [135], sensors [136], microbial agents [137], photoluminescence properties [137,138].…”
Section: α-Ag 2 Womentioning
confidence: 99%
“…Several synthesis methods are used in the preparation of FeWO 4 nanocrystals, but the conventional hydrothermal (CH) method has most often been employed and reported in the literature. [27][28][29][30] However, the CH method has some inconveniences, such as a long time period (typically one-half to several days) because of slow heat transfer due to the conduction and convection transport mechanism and high electric power usage (over a thousand watts). The solution to these problems is the microwave-hydrothermal (MH) method; this method facilitates the attainment of this oxide material in a shorter time and with lower energy consumption 31 which is possible due to efficient internal heating (in-core volumetric heating) by direct coupling of microwave irradiation with solvent molecules, ions and hydroxides in the reaction mixture.…”
Section: Introductionmentioning
confidence: 99%
“…4,[13][14][15] In particular, the relationship between morphology and gas sensing properties has been well established. 4,16,17 Tungsten-based oxides are an important class of materials that display wide potential functional properties, [18][19][20] speci-cally the silver tungstate (Ag 2 WO 4 ) compound, which can exhibit three different structures: a-orthorhombic, b-hexagonal, and g-cubic. [21][22][23][24][25] Recently, our research group reported a detailed study of the synthesis, structural and optical properties of hexagonal nanorod-like elongated a-Ag 2 WO 4 nanocrystals obtained by different methods.…”
mentioning
confidence: 99%